Use of iron mining tailings from dams for carbon nanotubes synthesis in fluidized bed for 17α-ethinylestradiol removal. (May 2020) - Silva, Rayane Cristian Ferreira; Ardisson, José Domingos; Cotta, Alexandre Alberto Chaves; Araujo, Maria Helena; Teixeira, Ana Paula de Carvalho
Abstract: This work reports the use of an iron ore tailings from waste dam as a catalyst and support for carbon nanotubes synthesis and their application in the adsorption of the 17α-ethinylestradiol hormone. The synthesis was carried out by Chemical Vapor Deposition (CVD) in a Fluidized Bed system using: ethylene at temperatures of 500, 600 and 700 °C, and acetonitrile at 500, 600, 700, 800 and 900 °C. The transmission electron microscopy (TEM) results showed that the two higher temperatures in each case favored the formation of nanostructures like carbon nanotubes (CNTs), with good yields. The ethylene source generated classic tubular structures of multiple walls. On the other hand, acetonitrile provided the formation of tubes with less organization, known as bamboo like. This morphology was caused by the insertion of nitrogen into the graphite structure (doping), which originates from the carbon source. The adsorptive capacity of the materials for 17α-Ethinylestradiol removal ranging from 9.2 mg g −1 to 22.3 mg g −1 . The kinetic and adsorption isotherm studies were also performed for the systems. As for kinetics, all of them presented pseudo-second order behavior. In relation to the type of isotherm, the systems showed Freundlich behavior, that is, the adsorption occurs in multiple layers. Finally, it was concluded that the use of an iron ore tail as a catalyst in the production of CNTs by CVD is feasible. The materials synthesized still had good adsorptive capacity for an emerging contaminant, thus this study allowed the investigation of two environmental problems. Graphical abstract: Image 1 Highlights: Iron mining tailings can be used to carbon nanomaterials synthesis by CVD process. A very problematic industrial waste has been turned into value-added material. The synthesized materials have a typical morphology of carbon nanotubes. Two carbon sources were used generating two classes of nanotubes. The synthesized materials were applied in the adsorption of the 17α-Ethinylestradiol. Abstract : Carbon nanotubes synthesis using iron waste from dams.